Stressors, associated responses, and coping strategies in professional esports players: A qualitative study - Leis, O.; Lautenbach, F.; Birch, P. D.; Elbe, A.-M. (International Journal of Esports, 2022)
To inform future intervention strategies and enhance professional esports players` performance, this qualitative study investigated stressors, associated stress responses, and coping strategies experienced by professional League of Legends players. Following criterion-based sampling, semi-structured interviews with 12 professional esports players were performed. The findings illustrate a variety of stressors related to team, performance, audience, and social media. Associated stress responses prior to competition (e.g., nervousness and excitement) seemed to be suppressed during competition, whereas post-competition responses were related to the outcome of competition. Although a range of strategies were identified, players most frequently communicated with teammates or coaches and focused on performance when coping with stressors. Study results show a need to teach players how to recognize and regulate associated stress responses, and to gain an in-depth understanding of stressors, coping strategies, and their effects on performance.